Business Intelligence For Local Mining Company Acknowledgement Reporting System - DivyaYadav, Dr. Naveen Choudhary (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The association of mining service firms ensures that every mining service firm (their members) works in accordance with the legislation and constitution. The issue in this association is that the job is to create queries for every data from tables in MySQL to create reports quickly, efficiently, and automatically for the government,domesticinvestorsand internationalinvestors, and any institutions that need information such as market needs, resource developments, and improvement of mining technologies. For example, how many metals are produced and invested in a month or year; metal trading, metal cost, for each mining company; and the amount of project in mining companies based on how many metals are extracted.Data Warehouse is a recommended solution because it has structured storage and can analyse data with IN-MEMORY OLAP, which can calculate live data and process and visualise data at high speeds.The design used the Customised Kimball Method to build the Data Warehouse, so this association company will be able to generate reports based on the needs of each situation.